Excerpta Medica abstracting journals: a case study of costs to medical school libraries. - La Rocco, A (1977)
A cost comparison study was made of Excerpta Medica's abstracting journals, based upon actual costs to a library. Unit costs were determined for six sections of EM as compared with six corresponding abstract journals. On average, EM sections were found to be 138% more costly than corresponding abstract journals. The effects of splitting of EM journal titles were also analyzed. This practice increases the price of a total subscription to EM and makes comprehensive information retrieval more difficult. A survey of medical school librarians as users of EM points to dissatisfaction with its increasing price, particularly when it results from title splitting.